Problematic aspects of modern professional training of pharmacy masters - N. O. Tkachenko; B. Р. Hromovyk (Zaporozhye State Medical University, 2022)
The aim of the research is to analyze the process of professional training of pharmacy master's in modern realities to identify problematic issues and find ways to solve them. Materials and methods. Critical analysis, content analysis, methods of generalization, and a combination of results were used in the work. Legal acts of the regulation of pharmaceutical education, data from the Unified State Database of education, 34 educational and professional programs for the preparation of pharmacy masters of 22 basic pharmaceutical institutions of higher education in the pharmaceutical direction were the material of the study. Results. The presence of a significant number of institutions of higher education was found. It leads to high costs per student due to the large volumes of their contingents in most institutions, as well as the likelihood of a slight global shortage and a decrease in the level of qualification. At the same time, there were no significant savings in training costs, which arises from the scale of activities. In addition, there is no proper state and public control over compliance with the institutions of higher education legal acts in the field of education and science. Analysis of the content of educational and professional programs revealed non-compliance with the legislation on the normative and variable part of the construction of the educational process and a significant variety of educational components. The existence of different approaches to the minimum number of credits for these components and graduation certification has been found. It will affect the process of integration of graduates into the international professional environment. It was shown that in a number of the institutions of higher education there was an inadequate qualification level of scientific and pedagogical workers in graduate departments and developers of the educational and professional programs. Conclusions. 78 institutions of higher education have been training pharmaceutical specialists on 23.02.2022. The proportion of part-time students among future specialists was characterized by an increase in the education level. Significant disagreements have been established among the cross-cutting educational and professional programs, according to which the training of Master of Pharmacy was carried out at the present stage. The ways of solving problematic issues of improving the educational space for the preparation of Master of Pharmacy were proposed.